Double-stranded RNA virus outer shell assembly by bona fide domain-swapping - Sun, Z; El Omari, K; Sun, X; Ilca, S; Kotecha, A; Stuart, D; Poranen, M; Huiskonen, J (Springer Nature, 2017)
Correct outer protein shell assembly is a prerequisite for virion infectivity in many multi-shelled dsRNA viruses. In the prototypic dsRNA bacteriophage φ6, the assembly reaction is promoted by calcium ions but its biomechanics remain poorly understood. Here, we describe the near-atomic resolution structure of the φ6 double-shelled particle. The outer T=13 shell protein P8 consists of two alpha-helical domains joined by a linker, which allows the trimer to adopt either a closed or an open conformation. The trimers in an open conformation swap domains with each other. Our observations allow us to propose a mechanistic model for calcium concentration regulated outer shell assembly. Furthermore, the structure provides a prime exemplar of bona fide domain-swapping. This leads us to extend the theory of domain-swapping from the level of monomeric subunits and multimers to closed spherical shells, and to hypothesize a mechanism by which closed protein shells may arise in evolution.